Ibrutinib With Rituximab in First-Line Treatment of Older Patients With Mantle Cell Lymphoma. Issue 2 (10th January 2022) - Jain, Preetesh; Zhao, Shuangtao; Lee, Hun Ju; Hill, Holly A.; Ok, Chi Young; Kanagal-Shamanna, Rashmi; Hagemeister, Fredrick B.; Fowler, Nathan; Fayad, Luis; Yao, Yixin; Liu, Yang; Moghrabi, Omar B.; et al.
Abstract : PURPOSE: Most patients with mantle cell lymphoma (MCL) are older. In this study, we investigated the efficacy and safety of a chemotherapy-free combination with ibrutinib and rituximab (IR) in previously untreated older patients with MCL (age ≥ 65 years). METHODS: We enrolled 50 patients with MCL in this single-institution, single-arm, phase II clinical trial (NCT01880567 ). Patients with Ki-67% ≥ 50% and blastoid morphology were excluded. Ibrutinib was administered with rituximab up to 2 years with continuation of ibrutinib alone. The primary objective was to assess the overall response rate and safety of IR. In evaluable samples, whole-exome sequencing and bulk RNA sequencing from baseline tissue samples were performed. RESULTS: The median age was 71 years (interquartile range 69-76 years). Sixteen percent of patients had high-risk simplified MCL international prognostic index. The Ki-67% was low (< 30%) in 38 (76%) and moderately high (≥ 30%-50%) in 12 (24%) patients. The best overall response rate was 96% (71% complete response). After a median follow-up of 45 months (interquartile range 24-56 months), 28 (56%) patients came off study for various reasons (including four progression, 21 toxicities, and three miscellaneous reasons). The median progression-free survival and overall survival were not reached, and 3-year survival was 87% and 94%, respectively. None of the patients died on study therapy. Notably, 11 (22%) patients had grade 3 atrial fibrillation. Grade 3-4 myelosuppression was seen in < 5% of patients. Differential overexpression of CCND1, BIRC3, BANK1, SETBP1, AXIN2, and IL2RA was noted in partial responders compared with patients with complete response. CONCLUSION: IR combination is effective in older patients with MCL. Baseline evaluation for cardiovascular risks is highly recommended. Randomized trial is needed for definitive conclusions.